Toronto's 'Vancouverism': developer adaptation, planning responses and the challenge of design quality. Issue 2 (March 2017) - White, James T.; Punter, John
Abstract : This paper examines 'Vancouverism' and its recent reproduction at CityPlace on Toronto's Railway Lands. The developers, Concord Pacific, were centrally involved in producing 'Vancouverism' in the 1990s and 2000s. This study examines the design quality of CityPlace and explores the differences between the planning cultures in Vancouver and Toronto. In evaluating the design outcomes, it highlights a mismatch between the public sector's expectations, the developer's ambitions and the initial design quality. The paper demonstrates that, despite an increasingly sophisticated system of control, the city of Toronto's ability to shape outcomes remains limited and, overall, the quality of development falls short of that achieved in Vancouver.